2020
DOI: 10.1111/jcmm.15999
|View full text |Cite
|
Sign up to set email alerts
|

The endoplasmic reticulum stress and the unfolded protein response in kidney disease: Implications for vascular growth factors

Abstract: Acute kidney injury (AKI) and chronic kidney disease (CKD) represent an important challenge for healthcare providers. The identification of new biomarkers/pharmacological targets for kidney disease is required for the development of more effective therapies. Several studies have shown the importance of the endoplasmic reticulum (ER) stress in the pathophysiology of AKI and CKD. ER is a cellular organelle devolved to protein biosynthesis and maturation, and cellular detoxification processes which are activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 125 publications
(153 reference statements)
0
23
0
Order By: Relevance
“…CKD is characterized by elevated inflammation, oxidative stress, and ischemia, which are persistent ER stress inducers that inevitably result in extra accumulation of misfolded or unfolded proteins in the ER. ER stress, including UPR and ERAD, are subsequently initiated to address the abnormally retained proteins [17,47]. Indeed, expressions of ER stress-and UPR-related genes are significantly increased and closely related with kidney function in CKD patients [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKD is characterized by elevated inflammation, oxidative stress, and ischemia, which are persistent ER stress inducers that inevitably result in extra accumulation of misfolded or unfolded proteins in the ER. ER stress, including UPR and ERAD, are subsequently initiated to address the abnormally retained proteins [17,47]. Indeed, expressions of ER stress-and UPR-related genes are significantly increased and closely related with kidney function in CKD patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…CKD is characterized by increased endoplasmic reticulum (ER) stress and concomitant with Klotho deficiency, indicating potential interplay between ER stress and Klotho expression [8,[17][18][19]. We previously observed that rats with unilateral ureter obstruction (UUO) induced-renal interstitial fibrosis (RIF) featured both ER stress ignition and Klotho loss, and Klotho replacement treatment repressed renal ER stress and improved their kidney function [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated the mechanism by which ER stress participates in various renal fibrosis processes, such as AKI, CKD, and AKI to CKD transition. Studies suggest that ER stress may play different roles in AKI and CKD [ 81 ]. On one hand, transient ER stress was found to trigger adaptive UPR to protect kidney in AKI.…”
Section: Role Of Vegf In Renal Fibrosismentioning
confidence: 99%
“…VEGF activated three UPR signaling pathways, but mainly stimulated PERK and ATF6 to promote cell survival and angiogenesis [ 85 ]. In turn, PERK also stimulated VEGF/VEGFR system [ 81 ]. UPR stimulated the expression of VEGF by ATF4 branch in human umbilical vein endothelial cells [ 86 ].…”
Section: Role Of Vegf In Renal Fibrosismentioning
confidence: 99%
“…Besides, mitochondria play a central regulatory role in endothelial metabolism, closely related to cell proliferation, apoptosis, and nuclear signal transduction ( Qi et al, 2017 ). In addition, mitochondria-associated ER membranes (MAMs), as a novel subcellular structure, have a more profound impact on endothelial function by regulating mitochondrial dynamics, lipid metabolism, and calcium signaling ( Ricciardi and Gnudi, 2020 ). It has been reported that MAMs have multiple roles in diabetic complications ( Wu et al, 2019 ; Cheng et al, 2020 ), but no endothelial cells have been concerned.…”
Section: Introductionmentioning
confidence: 99%